The Shifting of Burden of Proof on Corruption Offences in Indonesia After The Ratification of United Nations Convention Against Corruption (UNCAC) 2003 - Lilik Mulyadi; . Ismail (Postgraduate of Jayabaya University, 2016)
This article describes the result of a research regarding the shifting of burden of proof on corrup- tion offenses in the Indonesia after the ratification of United Nations Convention Against Corruption (UNCAC) 2003. T he article uses normative research which regulation, conceptual, case and compar- ative approach. Such research emphasizes interpretation and legal construction to obtain some legal norms, conception, regulation list and its implementation in concerto cases. Regulation and concep- tual approach to used how to know, existences, consistency and harmonization regarding the shifting of burden of proof upon corruption offenses in legislation body. The cases approach uses comparative law regarding the reversal burden of proof upon corruption offender between Indonesia and the other countries. This research shows that the shifting of burden of proof has never yet applied for in the corruption cases Indonesia. The Indonesian corruption regulation policy, especially article 12B, 37, 37A, 38B apparently it’s not cleaq and disharmony to norm of sudden charge of fortune the shifting of burden of proof formulation in connection with United Nations Convention Against Corruption 2003 (KAK 2003). So, necessary (needs) of modification sudden charge of fortune shifting of burden of proof formulation which preventive, represive and restorative characteristic.Keywords: Corruption; The Shifting of Burden of Proof; Balanced Probability of Principles